Cytotoxicity of zn-3mg biodegradable alloy for bone implant applications - Murni Nazira Sarian, 1988- author; Hendra Hermawan, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (2014)
Thesis (Sarjana Kejuruteraan (Bioperubatan)) - Universiti Teknologi Malaysia, 2014